Physiological, biochemical and molecular responses to water stress and rehydration in Mediterranean adapted tomato landraces. (5th September 2018) - Giorio, P.; Guida, G.; Mistretta, C.; Sellami, M. H.; Oliva, M.; Punzo, P.; Iovieno, P.; Arena, C.; De Maio, A.; Grillo, S.; Albrizio, R.
Abstract: Mediterranean tomato landraces adapted to arid environments represent an option to counteract drought, and to address the complexity of responses to water deficit and recovery, which is a crucial component of plant adaptation mechanisms. We investigated physiological, biochemical and molecular responses of two Mediterranean tomato landraces, 'Locale di Salina' (Lc) and 'Pizzutello di Sciacca' (Pz) under two dehydration periods and intermediate rehydration in greenhouse pot experiments. Relationship between CO2 assimilation ( A ) and stomatal conductance under severe water stress ( g s < 0.05 mol·m −2 ·s −1 ) indicated the occurrence of stomatal and non‐stomatal limitations of photosynthesis. Gas exchange promptly recovered within 2–3 days of rehydration. ABA and g s showed a strict exponential relationship. Both leaf ABA and proline peaked under severe water stress. Lc showed higher accumulation of ABA and higher induction of the expression of both NCED and P5CS genes than Pz. Poly(ADP‐ribose) polymerase increased during imposition of stress, mainly in Lc, and decreased under severe water stress. The two landraces hardly differed in their physiological performance. Under severe water stress, g s showed low sensitivity to ABA, which instead controlled stomatal closure under moderate water stress ( g s > 0.15 mol·m −2 ·s −1 ). The prompt recovery after rehydration of both landraces confirmed their drought‐tolerant behaviour. Differences between the two landraces were instead observed at biochemical and molecular levels.